Über die Abschätzung der Konvergenzschnelligkeit im integralen Grenzwertsatz im Falle des stabilen Grenzgesetzes - Mitalauskas, A. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. А. Миталаускас. Об оценке быстроты сходимости в интегральной предельной теореме в случае устойчивого предельного распределения A. Mitalauskas. Konvergavimo greičio įvertinimas integralinėje ribinėje teoremoje stabilaus ribinio dėsnio atveju